Graphene Oxide Decorated with Nickel Cobaltite Nanoparticles as an Adsorbent for Cationic Methyl Green Dye: Kinetic, Isotherm, and Thermodynamic Studies - Maryam Abdulsatar Abduljabar; Sundus Hadi Merza (مجلة بغداد للعلوم, 2024)
In this study, graphene oxide (GO) flakes were embellished with NiCo2O4 ‎‎(NC) nanoparticles by in situ deposition, and the produced composite (NC: ‎GO) was utilized as an adsorbent to remove methyl green dye (MG) from aqueous ‎solutions. The successful coating of graphene oxide with nickel cobaltite ‎nanoparticles (NC) was verified using FT-IR, SEM and X-ray diffraction (XRD) studies. ‎The crystalline particle sizes of NC nanoparticles and NC nanoparticles decorated ‎GO were 10.53 nm and 9.30 nm respectively. The impact of several experimental ‎factors, including time of contact, the dosage of adsorbent, and temperature were ‎investigated. The optimal contact time and adsorbent dosage were 120 minutes and ‎‎3 mg/L, respectively. The adsorption data fitted better to Freundlich isotherm. Four ‎kinetic models were used to track the adsorption process: a pseudo first-order ‎equation, a pseudo second-order equation, an intraparticle diffusion equation, and ‎the Boyd equation. Modeling of the experimental data revealed that the adsorption ‎kinetics was well represented by the pseudo-second order model(R2=0.9945) with a ‎rate constant of 3.2 ×10-3 (g/mg. min). MG dye is gradually absorbed by the NC ‎nanoparticles through intraparticle diffusion and is afterward held in smaller pores. ‎The values of the thermodynamic analysis showed that the MG dye adsorption was ‎an endothermic in nature, spontaneous and phyisorption process.‎